DOP18 UCEIS is associated with PRO2, partial Mayo and SCCAI remission in UC: Final results from a prospective study. (27th May 2021) - Golovics, P; Gonczi, L; Reinglas, J; Verdon, C; Pundir, S; Afif, W; Wild, G; Bitton, A; Bessissow, T; Lakatos, P L
Abstract: Background: Optimal management of patients with ulcerative colitis (UC) requires the accurate assessment of disease activity. Endoscopic evaluation is considered the gold standard approach, but it is invasive. We aimed to determine the operating characteristics of the Ulcerative Colitis Endoscopic Index of Severity (UCEIS), to quantify the cut off most closely correlated with clinical remission or activity and determine agreement with the Mayo endoscopic subscore (MES), Baron score, clinical scores and biomarkers. Methods: 171 patients were included prospectively and consecutively (age: 49 (IQR: 38–61) years, duration 12 (4–19)years, 79 females (46.2%), 57.3% extensive disease, 42.7% on biologicals) at the time of the colonoscopy. Ulcerative Colitis Endoscopic Index of Severity (UCEIS) Mayo endoscopic subscore (MES), Baron scores were calculated, as well as the 2 item patient reported outcome (PRO), partial MAYO, Simple Clinical Colitis Activity Index (SCCAI). C reactive Protein (CRP) and fecal calprotectin (FCAL) was available in 83 and 45.6% of patients. 17.0% had clinical flare, treatment was escalated in 14.6% of patients. Sensitivity, specificity, PPV and NPV values were calculated, ROC analysis and K-statistics were performed. Results: UCEIS was strongly associated to PRO2 SF (AUC:0.863), RBS (AUC:0.924), PRO2 combined (AUC:0.898), partial MAYO (AUC:0.945) and SCCAI (AUC:0.901) remission in a ROC analysis. A UCEIS of ≤3 was identified as the best cut-off to identify RBS subscore of 0, or total PRO2 remission (RBS 0 and SF ≤1), partial MAYO (≤2) and SCCAI (≤2.5) remission, while a UCEIS≥4 identified active disease frequently needing change in medical therapy. A moderate agreement was found between UCEIS <4 and MES 0 (K=0.471) or Baron 0 (K=0.414)/Baron 0–1 (K=0.353). Correlation between FCAL and UCEIS (coeff:0.701, p<0.0001) was strong, while modest only with CRP (coeff:0.248, p=0.01). Conclusion: UCEIS was strongly associated with clinical remission defined as PRO2, SF, RBS, partial Mayo or SCCAI with best agreement with RBS and partial Mayo remission. A UCEIS of ≤3 was identified as a cut-off for quiescent disease, while a UCEIS≥4 identified active disease, which can support clinical decision-making based on endoscopic findings. Agreement between UCEIS and FCAL was strong, while agreement with UCEIS and MES/Baron scores was moderate.